PENGARUH LIFESTYLE DAN WORD OF MOUTH TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN APLIKASI E- MONEY ’’DANA’’ DI KOTA BIMA - Basrin Haryanto; Ismunandar Ismunandar; Ita Purnama (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine lifestyle and word of mouth regarding consumer decisions using the e-money application ''dana''. This research uses observational research. The research results show that lifestyle variables have a partially significant effect on consumers' decisions to use the